2003
DOI: 10.1021/ie020397a
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical Modeling of Dispersion Polymerization of Methyl Methacrylate in Supercritical Carbon Dioxide

Abstract: Free-radical polymerization in supercritical carbon dioxide is a heterogeneous process that has recently attracted increased research and industrial interest. In the present paper, a comprehensive mathematical model is developed for the dispersion polymerization of vinyl monomers in supercritical CO2. A detailed kinetic mechanism is employed to describe the molecular weight development in the two-phase polymerization system. The concentrations of the various reacting species in the two phases as well as the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
34
2
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 18 publications
2
34
2
2
Order By: Relevance
“…The interphase radical transport, a key process in dispersion polymerization, was described by irreversible diffusion from the continuous phase to the polymer particles in both cases. The first comprehensive model of dispersion polymerization in scCO 2 has been reported by Chatzidoukas et al [22] This model is conceptually identical to that proposed by the same group for the suspension polymerization of poly(vinyl chloride) whereas the growing radical chains remain segregated in the phase where they were formed. [23] In a previous contribution [24] we showed that the latter model is unlikely to be applicable for the polymerization system under consideration when using reasonable parameter values and thus prompting us to develop a new model accounting for the detailed description of the radical interphase transport.…”
Section: Introductionmentioning
confidence: 54%
“…The interphase radical transport, a key process in dispersion polymerization, was described by irreversible diffusion from the continuous phase to the polymer particles in both cases. The first comprehensive model of dispersion polymerization in scCO 2 has been reported by Chatzidoukas et al [22] This model is conceptually identical to that proposed by the same group for the suspension polymerization of poly(vinyl chloride) whereas the growing radical chains remain segregated in the phase where they were formed. [23] In a previous contribution [24] we showed that the latter model is unlikely to be applicable for the polymerization system under consideration when using reasonable parameter values and thus prompting us to develop a new model accounting for the detailed description of the radical interphase transport.…”
Section: Introductionmentioning
confidence: 54%
“…However, although the modeling of CLRP in mass or dispersed phase water processes has been addressed for the case of RAFT polymerization, [18][19][20][21][22][23][24][25][26][27][28][29][30] and the modeling of conventional free-radical polymerization of vinylidene fluoride (VDF), [31,32] methyl methacrylate (MMA), [33,34] fluoromonomers [35] and styrene/divinylbenzene [36] in scCO 2 has already been addressed by several research groups, to the best of the authors' knowledge, there are no reports in the open literature about the modeling of CLRP processes carried out in scCO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…[30] Comprehensive models allow computation of the full molar mass distribution (for linear cases) by using phase equilibrium, a kinetic description of the reaction and mass transport calculations. [31][32][33][34] On the other hand, simplified models, such as the method of moments, and simple equilibrium calculations have been also used to describe the behavior of these simpler systems. [35][36][37] To the best of our knowledge, the modeling of copolymerization kinetics, molar mass development, and gel fraction evolution for vinyl/divinyl monomers in the presence of RDRP controllers, in scCO 2 , has not been addressed or has been addressed assuming a single phase situation.…”
Section: Doi: 101002/mats201700064mentioning
confidence: 99%
“…Number-and weight-average chain lengths for the sol fraction are calculated in terms of moments, as indicated in Equations (33) and (34). Molar mass dispersity (Ð) is calculated using Equation ( …”
mentioning
confidence: 99%